Teachings and Spreading of Zen Buddhism in Southeast Asia (Bodhi Path, 2024)
Zen Buddhism, also known as Chan Buddhism, originated in China during the Tang dynasty, and later spread to other parts of Asia, including Southeast Asia. While Zen is most closely associated with Japan, its influence and presence in Southeast Asia are notable and form an essential part of the region's religious and cultural landscape. Here is a detailed exploration of Zen Buddhism in Southeast Asia.
Keywords: Zen Buddhism; Mahayana Buddhism; Southeast Asia; China Buddhism; Korea Buddhism; Japan Buddhism; Vietnam Buddhism